2020
DOI: 10.3389/fendo.2020.00647
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hypercalcemia Crisis and Recurrent Acute Pancreatitis Due to Multiple Ectopic Parathyroid Carcinomas: Case Report and Literature Review of Mediastinal Parathyroid Carcinoma

Abstract: Mediastinal parathyroid carcinoma (PC) is a rare entity in primary hyperparathyroidism. The aim of this report is to demonstrate a case of mediastinal PC, and to provide a systemic literature review of this rare condition. A 34-year-old woman who had already undergone two cervical operations for hyperparathyroidism suffered from another recurrence, presenting with recurrent acute pancreatitis and persistent hypercalcemic crisis. Technetium-99 methoxyisobutylisonitrile imaging (MIBI) and computed tomography sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
4
0
2
Order By: Relevance
“…Clinical features that suggest a diagnosis of PC include age less than 50 years; markedly elevated PTH and calcium levels (usually >14mgdL), severe bone pain and lesions, and recurrent laryngeal nerve palsy from tumor invasion. 9 Most complications involve the skeletal and renal systems, although pancreatitis and hypercalcemic crisis may occur. 9 The Schulte 3 + 3 rule was initially developed for cervical PC, but it has been applied to mediastinal PC with 100% specificity and positive predictive value in ruling out malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical features that suggest a diagnosis of PC include age less than 50 years; markedly elevated PTH and calcium levels (usually >14mgdL), severe bone pain and lesions, and recurrent laryngeal nerve palsy from tumor invasion. 9 Most complications involve the skeletal and renal systems, although pancreatitis and hypercalcemic crisis may occur. 9 The Schulte 3 + 3 rule was initially developed for cervical PC, but it has been applied to mediastinal PC with 100% specificity and positive predictive value in ruling out malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Anamnese Aufgrund der o. g. pathophysiologischen Bedeutung kritischer Hyperkalzämien ist es besonders wichtig, neben einer symptomatischen Therapie zur Senkung des Serum-Kalziumspiegels [33] so schnell wie möglich die zugrunde liegende Ursache der Hyperkalzämie zu erkennen [7,11,14,24,32,34,35,36,37,38]. Hierzu sollte neben der genauen Eigenanamnese auch die Familienanamnese erfragt werden, um bei Malignomen oder PHPT genetisch bedingte Ursachen auszuschließen.…”
Section: Diagnose Der Zugrunde Liegenden Erkrankungunclassified
“…Bei der Suche nach einer oder mehreren vergrößerten Nebenschilddrüsen im Rahmen eines PHPT ist bei kritischer Hyperkalzämie häufig mit einer ektopen, auch intrathorakalen Lage beteiligter NSD zu rechnen [5]. Umgekehrt werden ektop gelegene NSD-Adenome und Nebenschilddrüsenkarzinome oft erst diagnostiziert, wenn sie zu einer kritischen Hyperkalzämie oder hyperkalzämischen Krise geführt haben [37,41].…”
Section: Diagnose Der Zugrunde Liegenden Erkrankungunclassified
“…The first case of mediastinal parathyroid carcinoma was reported by Weissman in 1957 [ 8 ] and we identified that there were only scattered reports published before 1982, which were not included in this review due to their inherent differences with current radiological examination and treatment methods [ 9 , 10 ]. Table 1 summarized 20 cases included in our final sample [ 11 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table 1 summarized 20 cases included in our final sample [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%